Coping with COVID-19: The Resilience and Transformation of Community-Based Tourism in Brunei Darussalam - Noorashid, Najib; Chin, Wei Lee (Sustainability, 2021)
The COVID-19 pandemic heavily impacted the travel and tourism industry, economies, livelihoods, public services, and opportunities globally. This is also observed in the small country of Brunei. As one of the few countries that have successfully mitigated COVID-19 transmissions, Brunei is slowly rebuilding its tourism industry through its community-based tourism (CBT). Following Sharma et al.’s resilience-based framework for reviving the tourism industry post-COVID-19 established in 2021, this study incorporates responses from semi-structured interviews with 16 local CBT owners on the challenges, the management, and the CBT initiatives during the height of the pandemic until today. These initiatives include diversifying more tour packages and utilising local resources and products. Despite the lockdown imposed by the government, which suspended businesses and restricted all travelling, local CBT operations flourished, generated more income for the owners, and created job opportunities for the community. Such efforts have caused the public to appreciate local cultures, the environment, and ultimately increase CBT experiences in the country. While shedding light on Brunei’s unique management of its tourism industry during the pandemic, this paper also demonstrates theoretical and conceptual contributions to the recent literature of resilient and transformational tourism and provide suggestions on how to manage CBT operations during these challenging times.